2011
DOI: 10.5897/ajb11.048
|View full text |Cite
|
Sign up to set email alerts
|

Yield and yield components of six canola (Brassica napus L.) cultivars affected by planting date and water deficit stress

Abstract: In order to study the effect of planting dates and different irrigation regimes on yield and yield components of six canola cultivars, an experiment was conducted in two growing seasons; 2008 to 2009 and 2009 to 2010. Six canola cultivars (Zarfam, GKH1103, GKH1605, GKH2005, GKH305 and GKH3705) were cultivated in two different dates (October 7th and November 6th) with two levels of irrigation regimes (irrigation after 60 mm evaporation from Class A evaporation pan and irrigation interrupting at flowering stage)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The high productivity observed in this work corroborates Sharghi et al (2011), who worked with six cultivars of Brassica napus (L.) in the canola crop, at different sowing times, and found results ranging from 1,548 to 5,930 kg ha -1 . In addition to nitrogen fertilization and spacing, productivity was benefited by climatic factors such as temperature and rainfall.…”
Section: Resultssupporting
confidence: 88%
“…The high productivity observed in this work corroborates Sharghi et al (2011), who worked with six cultivars of Brassica napus (L.) in the canola crop, at different sowing times, and found results ranging from 1,548 to 5,930 kg ha -1 . In addition to nitrogen fertilization and spacing, productivity was benefited by climatic factors such as temperature and rainfall.…”
Section: Resultssupporting
confidence: 88%
“…The sowing of fodder maize on 15 th April (S 1 ) registered the highest green fodder yield than the rest of the sowing dates (Table 2). Joshi et al (2013) and Shargi et al (2011) reported similar findings. Nitrogen, a crucial component of plant tissue associated with cell division and cell elongation.…”
Section: Effect Of Sowing Dates and Nitrogen Levels On Yield And Yiel...mentioning
confidence: 55%
“…For the winter crop like rapeseed-mustard, time of sowing plays a crucial role to mine the full genetic potential of a variety as it is a thermo sensitive and photo sensitive crop Chatterjee, 1988, Mondal et al, 1999). One month delay in sowing can decrease seed yield from about 10 to 50% in different cultivars (Shargi et al, 2011). So sowing time is an important agronomic manipulation for influencing crop growth and yield (Bana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%